Lipidomics Indicates the Hepatotoxicity Effects of EtOAc Extract of Rhizoma Paridis - Li, Chaofeng; Wang, Mingshuang; Fu, Tingting; Li, Zhiqi; Chen, Yang; He, Tao; Feng, Dan; Wang, Zhaoyi; Fan, Qiqi; Chen, Meilin; Zhang, Honggui; Lin, Ruichao; et al. (Frontiers in Pharmacology, 2022)
Rhizoma Paridis is a traditional Chinese medicine (TCM) commonly used in the clinical treatment of gynecological diseases. Previous studies have shown that aqueous extracts of Rhizoma Paridis exhibit some hepatotoxicity to hepatocytes. Here, using lipidomics analysis, we investigated the potential hepatotoxicity of Rhizoma Paridis and its possible mechanism. The hepatic damaging of different solvent extracts of Rhizoma Paridis on zebrafish larvae were determined by a combination of mortality dose, biochemical, morphological, and functional tests. We found that ethyl acetate extracts (AcOEtE) were the most toxic fraction. Notably, lipidomic responsible for the pharmacological effects of AcOEtE were investigated by Q-Exactive HF-X mass spectrometer (Thermo Scientific high-resolution) coupled in tandem with a UHPLC system. Approximately 1958 unique spectral features were detected, of which 325 were identified as unique lipid species. Among these lipid species, phosphatidylethanolamine (PE), cardiolipin (CL), Ceramide (Cer), lysophosphatidylinositol (LPI), sphingosine (Sph), etc., were significantly upregulated in the treated group. Pathway analysis indicates that Rhizoma Paridis may cause liver damage via interfering with the glycerophospholipid metabolism. Collectively, this study has revealed previously uncharacterized lipid metabolic disorder involving lipid synthesis, metabolism, and transport that functionally determines hepatic fibrosis procession.